Lewis Acidic Cationic Strontium and Barium Complexes - Thum, Katharina; Martin, Johannes; Elsen, Holger; Eyselein, Jonathan; Stiegler, Lisa; Langer, Jens; Harder, Sjoerd (European Journal of Inorganic Chemistry, 2021)
Lewis acidic (BDI)Ae+ cations of the heavier metals Sr and Ba, which are not stabilized by polar solvents, have been obtained by double deprotonation of (BDI)H2+ with either SrN’’2 or BaN’’2; BDI = HC[C(Me)N(DIPP)]2, DIPP = 2,6-diisopropylphenyl, Ae = alkaline earth, N’’ = N(SiMe3)2. Due to clathrate formation [(BDI)Ae+][B(C6F5)4−] could not be crystallized, but pyrene addition gave crystalline [(BDI)Ae+ ⋅ pyrene][B(C6F5)4−] which was structurally characterized for Ae = Mg, Ca, Sr, Ba. (R2N)Ae+ cations of the heavier metals Sr and Ba were obtained by reaction of Ae(NR2)2 with [Ph3C+][B(C6F5)4−] or [PhNMe2H+][B(C6F5)4−]. Following complexes were structurally characterized: [N’’Ba+ ⋅ (tol)2][B(C6F5)4−], [N*Sr+ ⋅ PhNMe2][B(C6F5)4−], [N*Ba+ ⋅ tol][B(C6F5)4−] and [N*Ba+ ⋅ C6H6][B(C6F5)4−]; tol = toluene and N* = N(SiiPr3)2. DFT calculations show that Sr⋅⋅⋅PhNMe2 coordination is preferred over Sr⋅⋅⋅toluene bonding. The (R2N)Ae+ cations can be used as Brønsted bases (reaction with (BDI)H gave (BDI)Ae+) and may be useful precursors for a variety of Lewis base-free RAe+ cations. DFT calculations, limited to monomeric model systems including B(C6F5)4− (ωB97XD/def2tzvpp//ωB97XD/def2svp), show that there is negligible electron transfer from the pyrene or toluene ligands to the Ae2+ cation. Electrostatic attraction originates from charge-induced polarization of the (Formula presented.) -electron density in the toluene and pyrene ligands.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Ab initio calculations; Arene coordination; Barium; Cations; Strontium